THE PSYCHOLOGICAL AND EDUCATIONAL DRIVERS OF INVESTMENT DECISIONS: A STUDY ON GEN Y AND GEN Z IN BATAM CITY - Marheni, Dewi Khornida; Serina, Serina; Hashim, Hanini Ilyana Che; Ramadani, Arienda Gitty (Universitas Nusa Cendana, 2025)
The primary purpose of this research is to thoroughly analyze the influence of overconfidence and herding behavior on stock investment decisions. Additionally, this research aims to investigate the moderating effect of financial literacy on the relationship between these behavioral factors (overconfidence and herding) and investment decisions. This research is quantitative research. The sample of this research is Gen Y and Gen Z stock investors in Batam City, Indonesia. The research analyzed the data using Partial Least Square Structural Equation Model (PLS-SEM), an advanced statistical technique that allows examining complicated relationships among observed variables and latent variables. The findings have revealed that overconfidence has a significant positive effect on investment. Similarly, herding significantly positively affects investment decisions, while financial literacy successfully moderates the relationship between overconfidence and investment decisions; however, it does not successfully moderate the relationship between herding and investment decisions. Keywords: Financial Literacy; Herding; Investment Decision; Overconfidence